Flexible Pseudocapacitive Iontronic Tactile Sensor Based on Microsphere‐Decorated Electrode and Microporous Polymer Electrolyte for Ultrasensitive Pressure Detection. (30th March 2022) - Wang, Peng; Li, Guoxian; Yu, Wei; Meng, Chuizhou; Guo, Shijie
Abstract: Wearable sensor as the initial terminal is in great requirement for people pursuing healthy life. High‐performance tactile sensors are the guarantee of accurate pressure information acquisition. Herein, a flexible iontronic tactile sensor is developed by utilizing a highly conductive poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) thin film decorated with polymethyl methacrylate microspheres as pseudocapacitive electrode and a porous polyurethane foam composited with Na + /Cl − ion‐enriched polyvinyl alcohol gel as polymer electrolyte through a facile method of solution‐casting followed by freeze‐drying. By taking advantages of both high pseudocapacitance and rationally designed microstructures, the developed tactile sensor shows an ultrahigh sensitivity (≈162.90 kPa −1 ), a broad detection range (≈160 kPa), a low detection limit (≈30 Pa), a fast response time (≈25 ms), and excellent repeatability and durability. Thanks to the ultrahigh sensitivity, the sensor is capable of detecting subtle pressures caused by dynamic micromotions such as touching a sandpaper surface, dropping water droplets, and adding water into a beaker. Application of a smart glove mounted with such sensor unit and array for a fast and accurate Braille recognition is also demonstrated. The proposed facile and efficient strategy of fabricating flexible ultrasensitive tactile sensors will be favorable to various wearable subtle pressure sensing applications. Abstract : A flexible iontronic tactile sensor is developed based on pseudocapacitive poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) electrode decorated with polymethyl methacrylate microspheres and porous polyurethane foam composited with sodium chloride/polyvinyl alcohol gel electrolyte. The ultrasensitive sensor is capable of detecting various subtle pressures. By attaching a sensor unit or array to the index fingertip, a smart glove is fabricated for an intelligent Braille recognition.